시설재배지에서 바이오차 연용이 토양의 화학적 특성 및 온실가스 배출에 미치는 효과 - 박재혁; Jae-hyuk Park; 김동욱; Dong-wook Kim; 강세원; Se-won Kang; 조주식; Ju-sik Cho (Hanguk hwangyeong nonghak hoeji, 2023)
Global concern over climate change, driven by greenhouse gas emissions, has prompted widespread interest in sustainable solutions. In the agricultural sector, biochar has emerged as a focal point for mitigating these emissions. This study investigated the impact of continuous biochar application on CO 2 and N 2 O emissions during the spring cabbage cultivation period. Greenhouse gas emissions in the biochar treatment groups (soils treated with 1, 3, and 5 tons/ha of rice husk biochar) were compared to those in the control group without biochar. During the spring cabbage cultivation period in 2022, the total CO 2 emissions were in the range of 71.6-119.0 g/m2day, and in 2023, with continuous biochar application, they were in the range of 71.6-102.1 g/m 2 day. The total emissions of N 2 O in 2022 and 2023 were in the range of 11.7-23.7 and 7.8-19.9 g/m2day, respectively. Overall, greenhouse gas emissions decreased after biochar treatment, confirming the positive influence of biochar on mitigating greenhouse gas release from the soil. Nevertheless, further research over an extended period exceeding five years is deemed essential to delve into the specific mechanisms behind these observed changes and to assess the long-term sustainability of biochar’s impact on greenhouse gas dynamics in agricultural settings.